2023
DOI: 10.1097/shk.0000000000002241
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering gut microbiota in patients with severe sepsis and septic shock

Se Ju Lee,
Dajeong Kim,
Hea Won Ann
et al.

Abstract: Introduction Gut microbiota dysbiosis is associated with susceptibility to sepsis and poor outcomes. However, changes to the intestinal microbiota during sepsis and their value as biomarkers are unclear. In this study, we compared the intestinal microbiota of patients with sepsis and healthy controls. Methods Stool was collected from patients with sepsis (subdivided according to mortality) and controls. Microbiome diversity and composition were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“… 24 Previous studies have found that the diversity and evenness of gut microbiota in sepsis group are lower than that in healthy control group. 25 , 26 In this study, shannon, simpson and shannoneven indices suggested that the diversity and evenness of gut microbiota in sepsis group were lower than that in healthy control group, which is consistent with previous reports. Among the organ dysfunction caused by sepsis, the gut is one of the most vulnerable organs.…”
Section: Discussionsupporting
confidence: 92%
“… 24 Previous studies have found that the diversity and evenness of gut microbiota in sepsis group are lower than that in healthy control group. 25 , 26 In this study, shannon, simpson and shannoneven indices suggested that the diversity and evenness of gut microbiota in sepsis group were lower than that in healthy control group, which is consistent with previous reports. Among the organ dysfunction caused by sepsis, the gut is one of the most vulnerable organs.…”
Section: Discussionsupporting
confidence: 92%
“…The liver and intestinal microbiomes have a close bidirectional relationship [37], and dysbiosis occurs in patients with liver cancer [38]. Moreover, the Shannon Index, which shows the diversity of the intestinal microflora, decrease owing to dysbiosis [39]. The Shannon index was lower in the MASH-HCC group than in the MASH group in this study.…”
Section: Discussionmentioning
confidence: 50%